Hemispheric Specialization for Processing the Communicative and Emotional Content of Vocal Communication in a Social Mammal, the Domestic Pig - Leliveld, Lisette M. C.; Düpjan, Sandra; Tuchscherer, Armin; Puppe, Birger (Frontiers in Behavioral Neuroscience, 2020)
In humans, speech perception is lateralized, with the left hemisphere of the brain dominant in processing the communicative content and the right hemisphere dominant in processing the emotional content. However, still little is known about such a division of tasks in other species. We therefore investigated lateralized processing of communicative and emotionally relevant calls in a social mammal, the pig (sus scrofa). Based on the contralateral connection between ears and hemispheres, we compared the behavioural and cardiac responses of 36 young male pigs during binaural and monaural (left or right) playback to the same sounds. The playback stimuli were calls of social isolation and physical restraint, whose communicative and emotional relevance, respectively, were validated prior to the test by acoustic analyses and during binaural playbacks. There were indications of lateralized processing mainly in the initial detection (left head turn bias, indicating right hemispheric dominance) of the more emotionally relevant restraint calls. Conversely, there were indications of lateralized processing only in the appraisal (increased attention during playback to the right ear) of the more communicative relevant isolation calls. This implies differential involvement of the hemispheres in the auditory processing of vocalizations in pigs and thereby hints at similarities in the auditory processing of vocal communication in non-human animals and speech in humans. Therefore, these findings provide interesting new insight in the evolution of human language and auditory lateralization.